2017
DOI: 10.1038/cdd.2017.166
|View full text |Cite
|
Sign up to set email alerts
|

TM9SF4 is a novel factor promoting autophagic flux under amino acid starvation

Abstract: Autophagy is a highly complicated process with participation of large numbers of autophagy-related proteins. Under nutrient starvation, autophagy promotes cell survival by breaking down nonessential cellular components for recycling use. However, due to its high complexity, molecular mechanism of autophagy is still not fully understood. In the present study, we report a novel autophagy-related protein TM9SF4, which plays a functional role in the induction phase of autophagic process. TM9SF4 proteins were abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…1i ). Taken together, these data showed that PPI induced autophagosome formation via TM9SF4-mTOR pathway, consistent with recent studies 30 , 32 .
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1i ). Taken together, these data showed that PPI induced autophagosome formation via TM9SF4-mTOR pathway, consistent with recent studies 30 , 32 .
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Cancer cells under microenvironmental stress (including low pH) use to cannibalize other cells 29 . TM9SF4 has been recently reported as an important regulator of autophagy 30 , 31 and cannibalism 29 . Suppression of TM9SF4 by siRNAs attenuated the PPI-stimulated dephosphorylation of mTOR, RPS6, and 4E-BP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TUNEL assay. TUNEL staining in tissue sections was conducted using the In Situ Cell Death Detection Kit (Roche, Switzerland) as described elsewhere 25 . Briefly, mASMCs were fixed with 4% paraformaldehyde (PFA) and permeabilized with 0.1% Triton X-100 in 0.1% sodium citrate.…”
Section: Methodsmentioning
confidence: 99%
“…TM9SF4 knockdown inhibits the cannibalism phenomenon (Lozupone et al, 2009). TM9SF4 can also regulate autophagy; it localizes to lysosomes and has been shown to regulate autophagy initiation in response to nutrient starvation by inhibiting the nutrient-sensing kinase complex mammalian target of rapamycin complex 1 (mTORC1), and it knockdown inhibits the autophagy (Sun et al, 2018). TM9SF4 is thought to suppress both cannibalism and autophagy, indicating a relationship between autophagy and cannibalism.…”
Section: Molecular Mechanism Of Cannibalismmentioning
confidence: 99%